Dilemma of State Sovereignty Protecting the Homeland Indonesia(Studies Agrarian Constitution) - FX. Sumarja (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
State of lawhas thesovereignauthoritytodetermineandregulatetheir ownaffairs for free. State of law teaches that all government action must be based on legislation drafted by the competent institution. Practice anomaly state in Indonesia, on the one hand have a sovereign law-making but on the other hand welcomed the intervention of other parties. The Conditions of legislators who still easily bought and intervention is one of the reasons. Impact the state is ineffective to protect the native land of Indonesia from foreign exploitation. Whereas the agrarian constitution of Indonesia sincerely as developing states have been prepared in line with the International Covenant on Economic, Social and Cultural Rights to set access restrictions by foreign agrarian resources.Legislation that opens wide agrarian access to foreign resources is a infringement of Human Rights, which should be corrected (judicial), hence it does not make pretending law states.Ostensiblyto protect thehomeland of Indonesia, althoughsoldto foreigners. Institutions authorized to make corrections to the laws that are discrepant with the constitution of agrarian is the Constitutional Court. This research subject points is to analyze legislation in the field of agrarian resources that have been corrected and the legal considerations.The study was conducted using the document approach. Such legal materials through library and internet access. Legal materials were examined using a prescriptive-analytical method.Until the beginning of2015there wereninelegislationrelated tothe field ofagrarian resourcesthat have beensuccessfullycorrected, andotherwisecontrary to theconstitution. So the Court's performance should be held up and requires awareness together in finding the national identity, became sovereign over agrarian resources and no intervention from other parties.